2019
DOI: 10.1186/s12917-019-2192-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bursin-like peptide as a potential virus inhibitor and immunity regulator in SPF chickens infected with recombinant ALV

Abstract: BackgroundAvian leukosis viruses (ALVs) are important contagious suppressive factors of chicken immunity and growth performance, resulted in enormous economic loss. Although virus eradication programs are applied in breeder flocks, ALVs are still widespread globally. Therefore, other valuable adjunct to reduce the negative effect of ALVs should be considered. Bursin-like peptide (BLP) showed remarkable immunomodulatory effects, whereas their influence on ALV-infected avian groups has not been reported. Here, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…This virus is also a naturally occurring avian virus that affects poultry worldwide causing enormous economic issues in the poultry industry since its emergence [80]. In this sense programs for virus eradication should be applied to reduce economic damage caused by ALVs [81].…”
Section: Avian Leukosis (Al)mentioning
confidence: 99%
See 2 more Smart Citations
“…This virus is also a naturally occurring avian virus that affects poultry worldwide causing enormous economic issues in the poultry industry since its emergence [80]. In this sense programs for virus eradication should be applied to reduce economic damage caused by ALVs [81].…”
Section: Avian Leukosis (Al)mentioning
confidence: 99%
“…Zeng et al (2019) evaluated a novel recombinant hybrid polypeptide based on bursin peptide. It was previously demonstrated that bursin, a tripeptide (Lys-His-Gly-NH2) hormone selectively stimulates avian B cell differentiation [81] and promotes immune-globulin (Ig) switching from IgM to IgG [9]. Furthermore, a novel stabilized bursin mimetics, Gagnon's tetrapeptide (Lys-Asn-Pro-Tyr), induces the selective expansion of B cells as well as the stimulation of cytotoxic T lymphocytes [10].…”
Section: Avian Leukosis (Al)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bursin is the first active factor with a clear tripeptide structure Lys-His-Gly-NH2 derived from BF, and selectively induces B-cell-differentiation [ 4 , 5 ]. Bursin-like peptide (BLP) is reported to have the potential as a virus inhibitor and immunity regulator to decrease the negative effects of ALV infection in SPF chickens [ 6 ]. BP-IV induces a strong humoural and cellular immune response for the epitope peptide vaccine for H9N2 subtype AIV [ 7 ].…”
Section: Introductionmentioning
confidence: 99%